The Furies - Book 20 - Connolly, John, 1968- (Thorndike, Maine : Center Point Large Print, 2022)
"Private investigator Charlie Parker is unwittingly drawn into a world of vengeance ... two separate -- but vitally connected -- investigations, which prove to be among the most complicated of his entire career. In The Sisters Strange, criminal Raum Buker arrives in Portland, Maine, only for a shocking act of theft to threaten not only his own existence but those of his former lovers -- the enigmatic sisters Strange. And in the title novel, The Furies, Parker must protect two women under threat as Portland shuts down in the face of a global pandemic. Unbeknownst to him, however, these clients are more capable of taking care of themselves than anyone could have imagined."--
The furies.
"A thriller"--Cover.
Keywords: Parker, Charlie "Bird" -- (Fictitious character) -- Fiction; Private investigators -- Fiction; COVID-19 Pandemic, 2020- -- Fiction; Sisters -- Fiction; Portland (Me.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Paranormal fiction; Suspense fiction